Semiotic analysis of Art Spiegelman’s Maus: A war comic with an open ending - Ravelo, Livia Carolina (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This paper proposes a semiotic analysis of some aspects of Maus, a war comic by Art Spiegelman, which is about Vladek Spielgeman’s life (Art’s father and survivor of the Jewish Holocaust) before, during and after Nazi Germany (1933-1945). This analysis explores the variation or continuity of the different signs which make up the language of comics, conceived as traces of varied recoverable discourses (Verón, 2004). For example, Spiegelman’s characters are anthropomorphic creatures, with an animal head and a human body, whose hybrid identity gives rise to multiple readings, such as the need for a deconstruction of the victim’s identity, the absence of any kind of sentimentalism and a new narrative about the classic confrontation “victim-murderer.”